Low-carbon agricultural technologies improve forage and feed production in the Caatinga biome, Brazil: Characteristics, comparison, effects of climate change, resilience, local development, and food security - Antunes de Mattos, Vanina Zini (2024)
Adjustments in Brazilian livestock are necessary to minimize greenhouse gas (GHG) emissions, since the largest source of methane comes from ruminants’ enteric fermentation, and of carbon from deforestation. Low-carbon agriculture technologies (LCAT) contribute to mitigating these emissions and this study evaluates the role of these technologies on ruminant forage production in Caatinga. A Strength, Weakness, Opportunity, and Threats analysis was used to elucidate the main features, followed by an Analytic Hierarchical Process, ranking the LCAT, and a risk analysis. Integrated Crop-Livestock-Forest System (ICLFS) is the most recommended technology, followed by Sustainable Forest Management (SFM) and Recovery of Degraded Areas with Pastures (RDA-P). The results can aid in the choice of the LCAT to be implemented by the smallholder in Caatinga, demonstrating the need to strengthen rural technical assistance, so that there is a real benefit to the producer and the environment.